Myelodysplastic Syndrome-Associated SRSF2 Mutations Cause Splicing Changes by Altering Binding Motif Sequences - Masaki, So; Ikeda, Shun; Hata, Asuka; Shiozawa, Yusuke; Kon, Ayana; Ogawa, Seishi; Suzuki, Kenji; Hakuno, Fumihiko; Takahashi, Shin-Ichiro; Kataoka, Naoyuki (Frontiers in Genetics, 2019)
Serine/arginine-rich splicing factor 2 (SRSF2) is a member of the SR protein family that is involved in both constitutive and alternative mRNA splicing. Mutations in SRSF2 gene are frequently reported in myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML). It is imperative to understand how these mutations affect SRSF2-mediated splicing and cause MDS. In this study, we characterized MDS-associated SRSF2 mutants (P95H, P95L, and P95R). We found that those mutants and wild-type SRSF2 proteins showed nuclear localization in HeLa cells. In vitro splicing reaction also revealed that mutant proteins associated with both precursor and spliced mRNAs, suggesting that the mutants directly participate in splicing. We established the human myeloid leukemia K562 cell lines that stably expressed myc-tagged wild-type or mutant SRSF2 proteins, and then performed RNA-sequence to analyze the splicing pattern of each cell line. The results revealed that both wild-type and mutants affected splicing of approximately 3,000 genes. Although splice site sequences adjacent to the affected exons showed no significant difference compared to the total exons, exonic motif analyses with both inclusion- and exclusion-enhanced exons demonstrated that wild-type and mutants have different binding sequences in exons. These results indicate that mutations of SRSF2 in MDS change binding properties of SRSF2 to exonic motifs and this causes aberrant splicing.